To a representation question Potamogetonaceae Dum. as a part of coastal and water vegetation (Experimental biology, 2016)
In this article keys definitions of generes and species of Potamogetonaceae Dum. family are given according to modern taxonomical system in a state language. In family the Potamogetonaceae Dum. of 3 generes: Potamogeton L., Ruppia L., Zannichellia L. and 24 species.Keys definition for 19 species of the generes Potamogeton L are made.: P. filiformis Pers., P. pamiricus Baagoe., P. macrocarpus Dobroch., P. pectinatus L., P. trichoides Cham. et Schlecht., P. compressus L. (L. zosterifolius Schum.; P. acutifolius Link., p.p.), P. obtusifolius Mert. et Koch., P. pusillus L., P. friesii Rupr., P. panormitanus Biv.-Bern., P. crispus L., P. perfoliatus L., P. praelongus Wulf., P. malaicus Miq., P. lucens L., P. natans L., P. nodosus Poir., P. alpinus Balb., P. gramineus L. (P. heterophyllus Schreb.); 3 species of the generes Zannichellia L.: Z. palustris L., Z. pedunculata Reichb., Z. major Boenn.; 2 species of the generes Ruppia L.: R. spiralis L., R. maritimа L. Potamogeton L. – multiyear aquatic plants; potamogetonaceae genus of the family. Individual shoots or plant parts floating freely in the water directly on the surface or under the water surface. The leaves are alternate, petiolate or sessile, of various shapes and sizes, from filamentous and linear to oval and almost round. There may be all or only submerged underwater and floating on the water surface. Inflorescence - spike gray-green or brownish-green color. Flowers bisexual, small, numerous, convergence or apart. Perianth of four rounded wing shares, four stamens without filaments. They flowering in July and August. There are two options pollination of flowers: inflorescences rise above the water, and the flowers are pollinated by the wind; inflorescences lie on the surface of the water, and if possible hydrophilicity and bestiality. Fruitlets with woody pericarp, consists of four stone-fruit shares. Vegetatively propagated and seeds. Seeds are spread by birds and water. Potamogeton L. - plant-cosmopolitan. They grow around the world in standing or slowly flowing fresh or brackish waters, often forming extensive thickets. They contain a lot of lime, and therefore can serve as fertilizer. Potamogeton L. eat aquatic mollusks, insects, fish. There, in the thickets of pondweed, their submarine parts, and sometimes at the bottom of the leaves, they spawn. Some species of Potamogeton L. serve as food for waterfowl, muskrats, beavers. Most fruitlets with woody pericarp are not so much for the food as for food mastication, being gastroliths. Mass development potamogeton in reservoirs complicates the movement of small vessels, helps to silting and overgrowing reservoirs.
Keywords: definition keys; genera; potamogetonaceae; species; water flora